Essentials of materials science and engineering - Askeland, Donald R.; Wright, Wendelin J. (Australia : Cengage Learning, 2014)
This text provides students with a solid understanding of the relationship between structure, processing and properties of materials. It covers fundamentals in an integrated approach that emphasizes applications of new technologies enabled by engineered materials.
1. Introduction to Materials Science and Engineering -- 2. Atomic Structure -- 3. Atomic and Ionic Arrangements -- 4. Imperfections in the Atomic and lonic Arrangements -- 5. Atom and Ion Movements in Materials -- 6. Mechanical Properties: Part One -- 7. Mechanical Properties: Part Two -- 8. Strain Hardening and Annealing -- 9. Principles of Solidification -- 10. Solid Solutions and Phase Equilibrium -- 11. Dispersion Strengthening and Eutectic Phase Diagrams -- 12. Dispersion Strengthening by Phase Transformations and Heat Treatment -- 13. Heat Treatment of Steels and Cast Irons -- 14. Nonferrous Alloys -- 15. Ceramic Materials -- 16. Polymers -- 17. Composites: Teamwork and Synergy in Materials -- 18. Electrochemical Corrosion -- Appendix A: Selected Physical Properties of Metals -- Appendix B: The Atomic and Ionic Radii of Selected Elements.
Includes index.
Keywords: MATERIALS; MATERIAL SCIENCE; MATERIAL SCIENCE -- PROBLEMS, EXERCISES, ETC